Pattern recognition and computer vision technologies in decision support systems of robotic systems - Lykho, T. A.; Sotnik, S. V. (Видавництво ОНТУ, 2024)
The paper discusses topical issues of intelligent technologies application in field of automation and robotics. The main approaches to processing of visual information in industrial environment are studied. The features of artificial intelligence algorithms functioning for analysis and interpretation of data obtained through sensors and cameras are analyzed. The key problems of adaptation of existing solutions to specific requirements of production processes are identified. A comparative analysis of pattern recognition various methods in computer vision for robotic systems is presented. The results of study are practical importance in further development and improvement of computer vision algorithms.
Keywords: pattern recognition; computer vision; decision support systems; robotic systems